Understanding How Language-Specific and Domain-General Resources Support Comprehension. Issue 7 (3rd October 2019) - Kopatich, Ryan D.; Magliano, Joseph P.; Millis, Keith K.; Parker, Christopher P.; Ray, Melissa
ABSTRACT: A large body of work has demonstrated that reader resources influence inference processes and comprehension, but few models of comprehension have accounted for such resources. The Direct and Mediational Inference model of comprehension (DIME) assumes that general inference processes mediate the effects of reader resources on general comprehension proficiency. The current study proposes an extension of DIME, the Inferential Mediation Model (IMM), to account for comprehension as it occurs while reading a particular text. College students were administered a battery of reader resource measures. In addition, they completed a think-aloud tool that measured comprehension and readers' inference processes while reading specific texts. A path analysis revealed that inference processes partially mediate the relationships between reader resources and comprehension performance. These results support the DIME and IMM, and suggest that inference processes that support mental model construction mediate the impact of reader resources on comprehension.